Microbial Metabolites in the Maturation and Activation of Dendritic Cells and Their Relevance for Respiratory Immunity - Wilson, Kayla R.; Gressier, Elise; McConville, Malcolm J.; Bedoui, Sammy (Frontiers in Immunology, 2022)
The respiratory tract is a gateway for viruses and bacteria from the external environment to invade the human body. Critical to the protection against these invaders are dendritic cells (DCs) - a group of highly specialized myeloid cells that monitors the lung microenvironment and relays contextual and antigenic information to T cells. Following the recognition of danger signals and/or pathogen molecular associated patterns in the lungs, DCs undergo activation. This process arms DCs with the unique ability to induce the proliferation and differentiation of T cells responding to matching antigen in complex with MHC molecules. Depending on how DCs interact with T cells, the ensuing T cell response can be tolerogenic or immunogenic and as such, the susceptibility and severity of respiratory infections is influenced by the signals DCs receive, integrate, and then convey to T cells. It is becoming increasingly clear that these facets of DC biology are heavily influenced by the cellular components and metabolites produced by the lung and gut microbiota. In this review, we discuss the roles of different DC subsets in respiratory infections and outline how microbial metabolites impact the development, propensity for activation and subsequent activation of DCs. In particular, we highlight these concepts in the context of respiratory immunity.